Activated carbons prepared from industrial pre-treated cork : sustainable adsorbents for pharmaceutical compounds removal - Mestre, Ana S. (2014)
Industrial pre-treated cork – granules of expanded corkboard, prepared from renewable biomass – was used for the first time as precursor for the preparation of eco-friendly activated carbons by chemical (K2CO3and KOH) and physical (steam) activation. Samples with different textural (microporosity/micro+mesoporosity) and surface chemistry (acidic/basic) were obtained. In the best compromise between porosity development/preparation yield, apparent surface areas ⩾900m2g−1were attained. Selected samples were assayed as adsorbents for the removal of pharmaceutical compounds (ibuprofen, paracetamol, acetylsalicylic acid, clofibric acid, caffeine and iopamidol). Kinetic results show that the steam activated carbon removes all the pharmaceutical compounds under study with removal efficiencies between 40% and 90%. Ibuprofen equilibrium adsorption isotherms showed that sample chemically activated with KOH at 800°C presents higher adsorption capacity (174.4mgg−1) and affinity for this target molecule than the steam activated and commercial samples. The overall results reveal that the lab-made carbons have adequate properties for pharmaceutical compounds removal, the results comparing favourably to those obtained with samples commercialized for water treatment purposes.